1999
DOI: 10.1093/humrep/14.1.167
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of in-vitro fertilization treatment in women with sonographic evidence of polycystic ovarian morphology

Abstract: This study compared the outcome of a course of up to three cycles of in-vitro fertilization (IVF) treatment in 46 women (97 cycles) who had polycystic ovaries (PCO) seen on ultrasound scan, but who had no clinical symptomatology associated with polycystic ovary syndrome, with that of 145 women (332 cycles) who had normal ovarian morphology on ultrasound examination. All 191 women had normal early follicular phase serum follicle stimulating hormone (FSH) concentrations, were less than 40 years of age and used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 27 publications
1
51
0
3
Order By: Relevance
“…This echoed the findings in some reported studies [10,[12][13][14][15], while some others have reported higher pregnancy rates in women with PCO compared to controls [9,11]. In contrast to some of the reported studies, our study made use of age-matched controls, which eliminated the confounding effect of age to the treatment outcome.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This echoed the findings in some reported studies [10,[12][13][14][15], while some others have reported higher pregnancy rates in women with PCO compared to controls [9,11]. In contrast to some of the reported studies, our study made use of age-matched controls, which eliminated the confounding effect of age to the treatment outcome.…”
Section: Discussionsupporting
confidence: 73%
“…There were a few studies on the IVF outcome of this group [9][10][11][12][13][14][15]. Some of these reported similar pregnancy or live birth rates in the isolated PCO group compared to controls [10,[12][13][14][15], whereas some reported higher pregnancy rates than controls [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…The reproductive performance of women undergoing IVF treatment with PCOS is characterized by their good response to ovarian stimulation that yields higher number of oocytes; however, with lower implantation and higher miscarriage rates (Engmann et al 1999, Ludwig et al 1999, Mulders et al 2003. Individual oocytes retrieved from nine women with PCOS and that from ten non-hirsute ovulatory women are used for microarray hybridization (Wood et al 2007).…”
Section: Global Gene Expression Changes During Loss Of Oocyte Qualitymentioning
confidence: 99%
“…Studies regarding the impact of PCOS or PCOM on oocyte competence are conflicting [28][29][30][31][32][33]. Many factors could have been responsible on this contradiction such as ovulation induction program, patient age and ethnicity [34], and BMI.…”
Section: Discussionmentioning
confidence: 99%